Microsatallite marker based characterization of indigenous pigs of Kerala - Ariprasath K (Department of Animal Breeding and Genetics, College of Veterinary and Animal Sciences, 2006)
The study was undertaken to assess the genetic diversity among four indigenous pig population of Kerala using microsatellite markers. The animals were selected from various part of Kerala, population I included the conserved Angamali pigs from university farm, Mannuthy, population II consisted of animals from Koothattukualm, population III were the animals from Ollur and animals from border districts of Kerala formed the population IV. Genetic analysis was carried out using five polymorphic microsatellite markers. Blood samples were collected from 100 unrelated indigenous pigs from all four populations and DNA was isolated. The phenol-chloroform method of extraction yielded 224.35±9.86µg/5ml of blood. PCR conditions were standardized for all five selected markers namely, S0005, S0101, SW1026, SW2517 and S0008. The forward primer of each marker was endlabelled with γ32 P-ATP as source of radio signal. The M13 single strand DNA was sequenced and used as a size standard. Autoradiography was employed to visualize the results. A total of eight alleles were detected in S0005 and S0101, five alleles in each of SW1026 and S0008, and six in SW2517. The heterozygosity varied from 0.7747 in SW2517 to as large as 0.8475 for S0005. The heterozygosity values for S0101, SW1026 and S0008 were 0.7774, 0.7672, and 0.7424 respectively. The PIC values ranges from 0.6974 for S0008 to 0.8291 for S0005. The PIC values for S0101, SW1026 and SW2517 were 0.7483, 0.7284 and 0.7381 respectively. The allele frequencies were used to estimate the Nei’s standard genetic distance among the populations. The distance measure ranged from 0.5704 to 0.7161, with the highest value noticed between population II and IV and the lowest between population I and III. A dendrogram was constructed using the POPGENE version 3.2 program which grouped the population I and IV in one cluster and II and III populations in another cluster.